2012
DOI: 10.1523/jneurosci.6008-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Impact of Voltage-Gated Calcium Channels and NMDA Receptors on Mitochondria-Mediated Neuronal Injury

Abstract: Glutamate excitotoxicity, a major component of many neurodegenerative disorders, is characterized by excessive calcium influx selectively through NMDA receptors (NMDARs). However, there is a substantial uncertainty concerning why other known routes of significant calcium entry, in particular voltage-gated calcium channels (VGCCs), are not similarly toxic. Here, we report that in the majority of neurons in rat hippocampal and cortical cultures, maximal L-type VGCC activation induces much lower calcium loading t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
80
0
8

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(89 citation statements)
references
References 43 publications
1
80
0
8
Order By: Relevance
“…An excess of Ca 2þ over the CRC threshold leads to the opening of the permeability transition pore in mitochondria followed by release of apoptotic factors, like cytochrome C (Stanika et al, 2012;Stout et al, 1998;Azarashvili et al, 2007). We hypothesize that during pathological elevations of intracellular Ca 2þ , mitochondria from INAD animals might readily undergo Ca 2þ overload and elicit neuronal cell demise.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…An excess of Ca 2þ over the CRC threshold leads to the opening of the permeability transition pore in mitochondria followed by release of apoptotic factors, like cytochrome C (Stanika et al, 2012;Stout et al, 1998;Azarashvili et al, 2007). We hypothesize that during pathological elevations of intracellular Ca 2þ , mitochondria from INAD animals might readily undergo Ca 2þ overload and elicit neuronal cell demise.…”
Section: Discussionmentioning
confidence: 98%
“…CRC is the maximal amount of Ca 2þ which mitochondria are able to accumulate. If mitochondria undergo a Ca 2þ overflow beyond the CRC, they open the permeability transition pore that is accompanied by complete depolarization and release of apoptotic factors, like cytochrome C (Stanika et al, 2012;Stout et al, 1998;Azarashvili et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with our experimental setup, these early studies did not include nifedipine (an antagonist for L-VGCCs) and CNQX (an antagonist for non-NMDA-type glutamate receptors) during NMDA stimulation. Because the activation of VGCCs (35)(36)(37)43) and non-NMDA-type glutamate receptors (38 -40) contributes significantly to excitotoxicity-induced Ca 2ϩ overload, NMDA stimulation without nifedipine and CNQX may impose a more severe pathological insult. It is possible that the protective effect from GluN2A inhibition may depend on the degree of the insults.…”
Section: Discussionmentioning
confidence: 99%
“…Specificity for the route of Ca 2 + influx in this process has additionally been shown by studies in which, Ca 2 + elevations of comparable magnitude induced by ionomycin, as measured with both high-and lowaffinity calcium-sensitive dyes, do not induce p47 phox phosphorylation or NOX2 activation in neurons (16). However, ionomycin-induced calcium elevations, to levels much higher than occur with NMDA receptor activation, can trigger neuronal superoxide production by mechanisms independent of NOX2 (16,165).…”
Section: Calcium Influx Through Nr2b-containing Nmda Receptorsmentioning
confidence: 92%
“…Calcium influx has long been established as a requisite event in excitotoxicity (29), but it has been difficult to resolve whether the route of calcium influx is important in this process (23,118,165). Tymianski and colleagues showed that NMDA-induced nitric oxide production requires calcium influx specifically through NMDA receptors (157,158).…”
Section: Calcium Influx Through Nr2b-containing Nmda Receptorsmentioning
confidence: 99%